Self-modeling and competitive diving performance - Rymal, Amanda (University of Ottawa (Canada), 2007)
The aim of this experiment was to investigate whether a self-modeling intervention could enhance competitive diving performance along with psychological mechanisms, such as self-efficacy, self-talk, and mental readiness. Eight participants (M age =12.6) competed at two competitions where one of their dives received the self-modeling video while the other acted as a control. At each competition, measures associated with the participants' self-efficacy, self-talk, mental readiness, and diving performance were collected. In addition, the participants responded to four questions relating to their thoughts and feelings of the self-modeling video intervention. Separate analyses of variance were conducted on all dependent measures. The results revealed no significant difference for all dependent measures between the self-modeling and control dive. This indicates that the self-modeling video failed to enhance competitive diving performance, and did not have an effect self-efficacy, self-talk, and mental readiness. Furthermore, imagery ability was measured to determine whether it acted as a possible moderating variable. However, this was not found to be a moderating variable between the self-modeling video and performance. Possible explanations for the lack of significant results with the quantitative data are forwarded A deductive analysis of the participants' transcripts was conducted where Zimmerman's (1989, 2000) self-regulation framework was adopted. Discussion of the qualitative data will focus on the participants' use of the self-modeling video with respect to self-regulatory processes.
Keywords: Health Sciences, Recreation.